The Effectiveness of Schema Therapy on Body Image, Suicidal Ideation, and Psychological Distress in Individuals Seeking Cosmetic Surgery: A Quasi-Experimental Study - Roshanzamiri, Fateme (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to determine the effectiveness of schema therapy on body image, suicidal ideation, and psychological distress among individuals applying for cosmetic surgery. This quasi-experimental study used a pretest–posttest design with a control group. The statistical population included individuals applying for cosmetic surgery who referred to Afra Counseling Center in Isfahan, Iran, in 2024. Thirty eligible participants were selected through convenience sampling and randomly assigned to an experimental group and a control group, with 15 participants in each group. The experimental group received schema therapy in twelve 90-minute sessions, while the control group received no intervention during the study period. Data were collected using the Body Image Concern Inventory, the Beck Scale for Suicide Ideation, and the Psychological Distress Questionnaire. Data were analyzed using multivariate and univariate analysis of covariance. The results of multivariate analysis of covariance showed a significant overall effect of group on the combined dependent variables after controlling for pretest scores, Pillai’s trace = .902, F(3, 23) = 70.92, p < .001, η² = .902. The results of univariate analysis of covariance indicated significant differences between the experimental and control groups in body image concerns, F(1, 27) = 144.24, p < .001, η² = .842; suicidal ideation, F(1, 27) = 51.69, p < .001, η² = .657; and psychological distress, F(1, 27) = 150.43, p < .001, η² = .848. These findings demonstrated that schema therapy significantly reduced body image concerns, suicidal ideation, and psychological distress in the experimental group compared with the control group. Schema therapy appears to be an effective psychological intervention for improving body image and reducing suicidal ideation and psychological distress among individuals applying for cosmetic surgery. These findings support the use of schema-based interventions as part of psychological assessment and counseling programs for cosmetic surgery applicants.